Ranah Domestik adalah Milik Bersama: Gender Equilibrium dalam Kartun Youtube “Bayi John” - Zakridatul Agusmaniar Rane (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2025)
Baby John is the YouTube content consisting of songs and videos that represent different messages. The songs tell direct messages about daily activities like brushing their teeth, washing hands, etc., while the video has an implied message about gender roles in the domestic sphere. This research investigated how the message of gender equilibrium is represented in a YouTube cartoon for toddlers,